Do Environmental Compliances Reduce Agricultural Profitability? An Inference from Indonesia - Abbas Ahmad (EDP Sciences, 2021)
This research seeks to find the effect of environmental compliances on profitability in the agricultural business sector. This research is quantitative by testing the nexus between environmental compliances (environmental cost and reputational incentive) and agricultural profitability. The sample of this study identified agricultural public firms in Indonesia including five sub-sectors consisting of farming, fisheries, livestock, plantation, and forestry. Financial statements and annual reports in terms of the environment were utilized in this research. Final samples were 12 public agricultural companies. The research model was analysed using the regression with common, fixed and random effect models and were checked the robustness using Generalized Method of Moment (GMM). The result of this research found no effects on the nexus between environmental cost and profitability. It indicates that the environmental cost spent by agricultural firms doesn’t reduce the profitability. The emerging effect can be found on reputational incentive leading the increase into the extent of agricultural profitability both return on assets and return on equity.